Learning Assistance in Quranic Reading Using the Wafa Method for Elementary School Students - Noprianti, Anis; Kustati, Martin; Gusmirawati, Gusmirawati (El-Rusyd, 2025)
The ability to read the Quran accurately and in accordance with tajwid rules is a fundamental competency for Muslim students. However, learning practices in elementary education indicate that many students still experience difficulties in mastering proper pronunciation (makhraj) and recitation rules, particularly due to limited opportunities for individual reading practice in heterogeneous classrooms. This study aims to examine the effectiveness of Quranic reading learning assistance using the Wafa Method. The research employed a Participatory Action Research (PAR) approach involving elementary school students in assisted Quranic reading activities. The Wafa Method was implemented through an integrative visual, auditory, and kinesthetic (VAK) approach, utilizing rhythm and movement as instructional media. The findings reveal that the application of the Wafa Method fostered a more engaging and participatory learning environment and significantly enhanced students’ motivation and Quranic reading abilities. Improvements were evident in reading fluency, accuracy of pronunciation, and adherence to tajwid rules. These results suggest that the Wafa Method is an effective and innovative alternative for Quranic education in elementary school contexts and holds potential for broader implementation in Islamic education.